Analisis pengaruh produktivitas tenaga kerja, ketimpangan pendapatan, dan investasi terhadap pertumbuhan ekonomi di Indonesia periode 2009-2018 - Dwi Desnasari (Jurnal Investasi Islam, 2020)
This study aims to analyze the effect of labor productivity, income inequality, and investment oneconomic growth in Indonesia. The data used is panel data consisting of time series data for 2009 -2018 and a cross section of 34 provinces in Indonesia. The variables used are economic growth,labor productivity, income inequality, and investment. The analysis tool used is panel dataregression, namely the Fixed Effect Model (FEM). The results showed that labor productivity had apositive and significant effect on economic growth, income inequality had a negative andsignificant effect, while investment had no effect on economic growth in 34 provinces in 2009-2018.